Deconstructing Gender Roles in Pygmalion An Examination of Criticism and Transformation - Ishfaq Majeed Mir (Formosa Journal of Science and Technology, 2023)
George Bernard Shaw's play "Pygmalion" has long been lauded for its astute commentary on social class and the transformative power of education. However, beneath its surface, the play also serves as a rich ground for the critique of traditional gender roles. The study delves into the nuanced examination of gender roles within the narrative, shedding light on the complex interplay between gender identity, societal expectations, and individual agency. Through a comprehensive analysis of the characters, especially Eliza Doolittle, and their relationships, this study explores how Shaw's work challenges and redefines traditional gender constructs. Furthermore, it highlights the ways in which "Pygmalion" engages with feminist themes, offering a fresh perspective on a classic text and its enduring relevance in the discourse surrounding gender and identity.